Redesigning Research Guides: Lessons Learned from Usability Testing at the University of Memphis. - McClure, Jessica; Hess, Carl; Marsicano, David (Information Technology & Libraries, 2023)
At the University of Memphis, a team of librarians and library staff formed the Research Guides Redesign Team (RGRT) to redesign, organize, and evaluate the University Libraries' (UL) research guides. The purpose of the project was to ensure that the new design of the research guides homepage was intuitive to use. While it is impossible to ensure absolute usability for every user, this usability study attempts to eradicate the most common interface issues in community experiences at the University of Memphis. The RGRT conducted usability testing to evaluate the effectiveness of the new standardized format, grouped headings, and the appearance of the interface. The RGRT worked within the limitations of Springshare's software to create the design and then chose five users to complete various task scenarios. Upon analysis of the users' ability to complete the tasks, the RGRT discovered that overall, the design was effective, but they did make a few minor changes. This study describes the process and includes the original design, the new design, edits made after usability testing was conducted, and plans for future testing.